INSIGHTS FROM THE EXECUTIVE BRANCH: FELLOW EXPERIENCES IN FEDERAL AGENCIES AND ORGANIZATIONS. (11th November 2018) - Burke, R; Frank, L; Sun, F; Golden, A; O'Hare, A; Fabiny, A
Abstract: Dr. Burke will summarize the collected insights and opinions related to health and aging of Fellows from placements at the National Institute on Aging, the Center for Medicare and Medicaid Services' Innovation Center and Office of the Duals, the Agency for Healthcare Research and Quality, the Veteran Affairs Administration, and the World Health Organization. Topics covered will include healthy aging program implementation, Older Americans Act reauthorization, housing and poverty, Alzheimer's disease and dementia care, and the opioid crisis.